2020
DOI: 10.1371/journal.pone.0234517
|View full text |Cite|
|
Sign up to set email alerts
|

Colonization of human opportunistic Fusarium oxysporum (HOFo) isolates in tomato and cucumber tissues assessed by a specific molecular marker

Abstract: Fusarium oxysporum is a large complex cosmopolitan species composed of plant pathogens, human opportunistic pathogens, and nonpathogenic isolates. Many plant pathogenic strains are known based on host plant specificity and the large number of plant species attacked. F. oxysporum is an opportunistic pathogen in humans with a compromised immune system. The objectives of this study were: (1) to develop a specific marker to detect human opportunistic F. oxysporum (HOFo) isolates; (2) to determine whether or not HO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Herein, the fungicidal activity of the essential oil obtained from the peels of Citrus lemon , Citrus aurantifolia , Citrus maxima , and Citrus sinensis were assessed against seven pathogenic fungi that have been reported as pathogenic to humans too [ 16 , 17 , 18 , 19 ], namely Rhizoctonia solani , Sclerotium rolfsii , Fusarium solani , Fusarium oxysporum , Fusarium semtectium , Botrytis cinerea , and Alternaria alternata . In the presented study, a nano-based valorization approach is reported to establish a novel hexosomal system containing the most active essential oil, allowing for an enhancement of the efficiency of natural fungicides, reducing costs and increasing competitiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, the fungicidal activity of the essential oil obtained from the peels of Citrus lemon , Citrus aurantifolia , Citrus maxima , and Citrus sinensis were assessed against seven pathogenic fungi that have been reported as pathogenic to humans too [ 16 , 17 , 18 , 19 ], namely Rhizoctonia solani , Sclerotium rolfsii , Fusarium solani , Fusarium oxysporum , Fusarium semtectium , Botrytis cinerea , and Alternaria alternata . In the presented study, a nano-based valorization approach is reported to establish a novel hexosomal system containing the most active essential oil, allowing for an enhancement of the efficiency of natural fungicides, reducing costs and increasing competitiveness.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, alarms have been raised in the health sector because FOSC is the second most common and virulent fungus reported, generating pathologies such as keratitis, onychomycosis, dermatitis, and allergies 37 , 38 . Wang et al (2020) reported that FOSC isolated human pathogens could colonize plants without causing disease; therefore, these may be silent reservoirs, increasing the risk of immunosuppressed patients coming into contact with or consuming contaminated fruits and plants; the authors suggest the possibility of gene exchange between a pathogenic strain with a non-pathogenic one, giving virulence to ubiquitous plant fungi 39 . According to Zuriegat et al .…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] Fusarium is a genus of filamentous fungi, which was found in a variety of habitats, such as water sources, soil, or with plants. [3,4] Fusarium oxysporum is the most common and economically important species which include both pathogenic [5] (plant, human, and animal) and non-pathogenic strains. As we known, some strains of F. oxysporum were reported as potential biological control agents, which had biological control activity against fungi, pests and certain insects.…”
Section: Introductionmentioning
confidence: 99%